Meningkatkan Return Saham: Peran Kepemilikan Manajerial, Profitabilitas, Leverage dan Ukuran Perusahaan - Atim Purwaningrat; I Gusti Agung Arista Pradnyani (MOTIVASI, 2025)
Purpose– This study aims to analyze the effect of managerial ownership, profitability, leverage, and company size on stock returns, as well as to provide scientific references for the development of further academic studies. In addition, this study is expected to enrich practical insights for companies in formulating more effective financial strategies to increase stock value and attract investor interest. Design/methodology– This research was conducted on companies engaged in the Property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2022–2023. Sample selection was carried out through a purposive sampling technique, namely by setting certain criteria that are adjusted to the research needs so that a total of 40 companies were obtained with a total of 80 observation units of analysis. The data analysis used is quantitative analysis. The analysis technique uses multiple linear regression analysis with the help of the SPSS version 26 application. Findings - Based on the data processing that has been done, it was found that managerial ownership did not show a significant effect on stock returns, while profitability was proven to have a positive effect on stock returns. On the other hand, leverage showed a negative relationship to stock returns, while company size had a significant positive effect on stock returns. For future research development, it is recommended to consider adding other independent variables such as earnings per share, financial distress, earnings management practices, or dividend policies, in order to obtain more comprehensive and representative results.